Exploiting polymorphism in second sphere coordination: thermal transformation, NLO properties and selective mechanochemical synthesis. Issue 14 (18th March 2016) - Yu, Hai-Bin; Li, Hai-Tao; Zhang, Peng; Famulari, Antonino; Guo, Fang; Bargigia, Ilaria; Martí-Rujas, Javier
Abstract : Polymorphism has been explored in a second sphere adduct using a racemic ligand that also shows racemic polymorphic behavior. The polar nature of the second sphere adduct allowed us to study NLO phenomena. Abstract : The racemic organic building block L acting as a first sphere ligand yields a new second sphere adduct [LH] + ·[FeCl4 ] − crystallizing as racemic polymorphs α and β. Solid-state DFT calculations show that polymorph β is the kinetic adduct as observed experimentally. The β-phase crystallizes in the polar space group Pna 21 and displays NLO properties. Mechanochemical synthesis yields only the β-phase.